Keluarga dalam Bisnis dan Biaya Utang: Bukti dari Perusahaan Keluarga di Indonesia - Imam muslim, Ade; Maghriby, Bimbim; Ramdani, Dani (Universitas Swadaya Gunung Jati, 2024)
The issue of efficiency in choosing funding sources has become a concern for researchers, especially during the Covid 19 pandemic. Our research seeks to investigate whether family involvement and ownership can contribute to funding efficiency, especially from debt. Then we extended the test to see if earnings management behavior could affect family involvement and ownership. For this purpose, we collect family companies that are listed on the Indonesia Stock Exchange for the period 2005 to 2020. The method we use is panel data regression analysis. The results of the study prove that family involvement in management and share ownership is able to contribute to reducing the cost of debt during the covid 19 pandemic. The results also provide empirical evidence that earnings management carried out through abnormal cash flows does not affect family involvement and ownership in contributing to lowering the cost of debt. This research is expected to provide implications for family companies, especially in determining funding decisions from debt schemes.